PENGARUH CAR, NPL, BOPO, LDR DAN RETURN ON ASSET TERHADAP PERTUMBUHAN LABA PADA BANK BUMN - Utami, Nurul; Hartono, Arif; Ulfah, Ika Farida (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to determine and understand the effect of CAR, NPL, BOPO, LDR, and ROA on Profit Growth. The method of analysis in this study is CAR, NPL, BOPO, LDR, and ROA which are seen to have partial and simultaneous effects on Profit Growth. The results show that CAR has a positive effect on profit growth, it means that if CAR increases, Profit Growth also increases. Furthermore, NPL has a positive effect on profit growth, this means that if NPL increases, Profit Growth also increases. Meanwhile, the BOPO variable has a positive effect on profit growth, it means that if the BOPO increases, the Profit Growth will also increase. Furthermore, LDR has a positive effect on profit growth, it means that if LDR increases, Profit Growth also increases. The fifth shows that ROA has a positive effect on profit growth, this means that if ROA increases, Profit Growth also increases. The results of the sixth hypothesis show that CAR, NPL, BOPO, LDR, ROA have a positive effect on Profit Growth.